What is the impact of obtaining medical clearance to participate in a randomised controlled trial examining a physical activity intervention on the socio-demographic and risk factor profiles of included participants? - Duncan, M. J.; Rosenkranz, Richard R.; Vandelanotte, C.; Caperchione, C. M.; Rebar, A. L.; Maeder, A. J.; Tague, R.; Savage, T. N.; van Itallie, A.; Mummery, W. K.; Kolt, G. S. (My University, 2017)
Background: Requiring individuals to obtain medical clearance to exercise prior to participation in physical activity interventions is common. The impact this has on the socio-demographic characteristic profiles of participants who end up participating in the intervention is not clear. Methods: As part of the multi-component eligibility screening for inclusion in a three-arm randomised controlled trial examining the efficacy of a web-based physical activity intervention, individuals interested in participating were required to complete the Physical Activity Readiness Questionnaire (PAR-Q). The PAR-Q identified individuals as having lower or higher risk. Higher-risk individuals were required to obtain medical exercise clearance prior to enrolment. Comparisons of the socio-demographic characteristics of the lower-and higher-risk individuals were performed using t tests and chi-square tests (p = 0.05). Results: A total of 1244 individuals expressed interest in participating, and 432 were enrolled without needing to undergo further screening. Of the 251 individuals required to obtain medical clearance, 148 received clearance, 15 did not receive clearance and 88 did not return any form of clearance. A total of 105 individuals were enrolled after obtaining clearance, and the most frequent reason for being required to seek clearance was for using blood pressure/heart condition medication. Higher-risk individuals were significantly older, had a higher body mass index and engaged in more sedentary behaviour than lower-risk individuals. Conclusions: Use of more inclusive participant screening protocols that maintain high levels of participant safety are encouraged. Allowing individuals to obtain medical clearance to participate can result in including a more diverse population likely to benefit most from participation.
Citation: Duncan, M. J., Rosenkranz, R. R., Vandelanotte, C., Caperchione, C. M., Rebar, A. L., Maeder, A. J., . . . Kolt, G. S. (2016). What is the impact of obtaining medical clearance to participate in a randomised controlled trial examining a physical activity intervention on the socio-demographic and risk factor profiles of included participants? Trials, 17, 6. doi:10.1186/s13063-016-1715-4
Keywords: Randomised Controlled Trial; Recruitment; Medical Clearance; Physical; Activity; Participant Characteristics